(untitled) (Bangladesh Heart Journal, 2022)
Background: Non ST - segment elevation myocardial infarction is heterogeneous in its presentation and is a major life-threatening cause of emergency medical care and hospitalization. Patients with non ST-segment elevation myocardial infarction are at risk for adverse cardiac events and if associated with increased age, it become a strong predictor of adverse cardiac events in patients with non ST-segment elevation myocardial infarction. Objective: To find out in - hospital outcome and severity of coronary artery disease of older patient with non - ST segment elevation myocardial infarction. Methods: This was a descriptive cross sectional study. The study was carried out in the department of cardiology, National Heart Foundation Hospital and Research Institute from June 2011 to May 2012. Patients of non ST - segment elevation myocardial infarction admitted at National Heart Foundation & Research Institute who fulfill the inclusion criteria were the study population. Patients were recruited by nonrandom sampling. One hundred and thirty four patients were recruited in this study. Data were prospectively collected in a pre - designed data collection form and analyzed by using SPSS - 16 software. Results: In this study patients had a greater prevalence of hypertension, diabetes mellitus. Chest pain and shortness of breath were common presentations observed in study patient during admission. They had a lower left ventricular ejection fraction than their younger counter parts. Older group was associated with an increased risk of triple vessel disease. In-hospital complications were significantly higher in older patients. Duration of hospital stay was longer in older patients. Conclusion: Older patients with non- ST segment myocardial infarction strongly predicts adverse inhospital outcome and severe coronary artery disease profile. Older patients should alert physicians to an increased risk of morbidity and mortality, which may in turn support more judicious treatment including appropriate utilization of cardiovascular diagnostic tests and therapeutics used in current cardiovascular care to optimize outcomes in these high-risk patients. Bangladesh Heart Journal 2022; 37(1): 52-58